Gravitino dark matter and neutrino masses with bilinear R-parity violation (2012)
ABSTRACT: The origin of neutrino masses and mixing and the nature of dark matter are two of the most elusive open problems of modern particle physics and cosmology, which clearly indicate the need for new physics beyond the standard model. It has been suggested that these two apparently unrelated issues may be closely interlinked. Here we propose an alternative way to relate dark matter with neutrino properties within a scenario where supersymmetry (SUSY) is the origin of neutrino mass, thanks to the spontaneous violation of R parity. For definiteness and simplicity we adopt an effective description in terms of explicit bilinear R-parity violating superpotential terms (BRpV)